Social Media Profiles:Extended Self, Ideal Self, Amended Self or a True Reflection of Consumer Personality. - Iftikhar, Maha (2014)
Four types of self which potentially are displayed on social media platforms are discussed: the true self, the extended self, the ideal self, and the amended self. The theory of the amended self is a new theory proposed in this study as there is no literature or current theoretical framework establishing the existence of such a type of self. The study also explores the impact of employment on social media usage, specifically focusing on Facebook profiles. 170 respondents participated in a quantitative survey to determine the relationships between the types of self potentially displayed on Facebook and their employment status. Students formed the largest group in the sample, with employed participants second, and self-employed, homemaker and unemployed, third, fourth and fifth respectively. Respondents were most in agreement with statements suggesting their Facebook profiles displaying their true self and most in disagreement with statements suggesting their Facebook profile represents their ideal self. It was found that employment status has no relationship to the extended self or ideal self being displayed online. There was also no correlation between most of the employment status sub-categories and the true or amended self being displayed on Facebook. The only two relationships established were between the employment status sub-category ‘Self-employed’ and Facebook profiles being a true reflection of consumer personality and the employment status sub-category ‘Homemaker’ and users’ Facebook profiles displaying an amended self.